Breast cancer therapy by laser-induced Coulomb explosion of gold nanoparticles - Ashiq, Muhammad Gul Bahar; Saeed, Mohammad Alam; Tahir, Bashir Ahmad; Noorddin, Ibrahim; Nadeem, Muhammad (Chinese Journal of Cancer Research; Vol 25, No 6 (December 26, 2013): Chinese Journal of Cancer Research, 2013)
Objective: Laser-induced Coulomb explosion of gold nanoparticles for breast cancer has been studied by nanophotolysis technique. This study aimed to investigate whether laser-induced bubble formation due to Coulomb explosion can provide an effective approach for selective damage of breast cancer with gold nanoparticles. Method: Numerical method involves laser-induced Coulomb explosion of gold nanoparticles. Different parameters related to nanophotolysis such as laser fluence, tumor depth, cluster radius, laser pulse duration, and bubble formation is studied numerically. Numerical simulation was performed using Mat lab. Results: The gold nanoparticles of 10, 20, 30, 40, and 50 nm in radius could penetrate into tumor 1.14, 1.155, 1.189, 1.20 and 1.22 cm in depth respectively. The maximum penetration depth in tumor could be obtained with nanoparticles of 50 nm radius. Short laser pulse of 40 ns with nanoparticles of 10 nm radius could penetrate into tumor 1.14 cm in depth. Bubbles with a radius of 9 μm could effectively kill breast cancer cells without damaging healthy ones. The bubble radius increased from 4 to 9 μm with an increase in pulse duration in the range of 10 to 30 ns. Conclusions: Gold nanoparticles with increasing radius and bubble formation for selective damage of breast cancer cells are successfully probed. The present calculated results are compared with other experimental findings, and good correlation is found between the present work and previous experimental values. It was demonstrated that bubble formation in tumor may further increase the efficacy of breast cancer treatment.